COMPUTER SIMULATION THE MECHANICAL MOVEMENT BODY BY MEANS OF MATHCAD - Leonid Flehantov; Anatolii Antonets (Kherson State University, 2017)
Here considered the technique of using computer mathematics system MathCAD for computer implementation of mathematical model of the mechanical motion of the physical body thrown at an angle to the horizon, and its use for educational computer simulation experiment in teaching the fundamentals of mathematical modeling. The advantages of MathCAD as environment of implementation mathematical models in the second stage of higher education are noted. It describes the creation the computer simulation model that allows you to comprehensively analyze the process of mechanical movement of the body, changing the input parameters of the model: the acceleration of gravity, the initial and final position of the body, the initial velocity and angle, the geometric dimensions of the body and goals. The technique aimed at the effective assimilation of basic knowledge and skills of students on the basics of mathematical modeling, it provides an opportunity to better master the basic theoretical principles of mathematical modeling and related disciplines, promotes logical thinking development of students, their motivation to learn discipline, improves cognitive interest, forms skills research activities than creating conditions for the effective formation of professional competence of future specialists.